COVID-19 challenges, responses, and resilience among rural Black women: a study protocol - Shan Qiao; Shan Qiao; Sara Wilcox; Sara Wilcox; Bankole Olatosi; Bankole Olatosi; Xiaoming Li; Xiaoming Li (Frontiers in Public Health, 2023)
Despite the aggregated burdens and challenges experienced by rural Black women during the COVID-19 pandemic, many likely also demonstrated strength and resilience to overcome challenges. A mixed methodology and a community-based participatory approach will be used to collect multilevel data on challenges, responses, resilience, and lessons during the pandemic from Black women, community health workers, and community leaders in rural areas in South Carolina (SC). Specifically, the unique circumstances and lived experiences of rural Black women during the COVID-19 pandemic will be documented to understand their needs regarding effective management of social, physical, and mental health challenges through focus group discussions and in-depth interviews with Black women, community health workers, and local community leaders recruited from rural SC communities. Barriers, facilitators, and potential impacts of multilevel resilience development will be identified through a survey administered among rural Black women recruited from 11 rural counties (with one as site for a pilot testing of the questionnaire). A report for public health practice will be developed, including recommended strategies to optimize health systems' emergency preparedness and responses through triangulation of qualitative and quantitative data from multiple sources. Findings in the proposed study will provide valuable references in terms of addressing social determinants of health factor challenges during the pandemic, fostering resilience, and informing evidence-based decision-making for policymakers. The study will contribute to the development of public health emergency preparedness plans, which can promote the resilience of women, their families, and local communities as well as optimize effective preparedness and response of health systems for rural Black women and their families during infectious disease outbreaks and other public health emergencies.